2008
DOI: 10.1021/ic8016886
|View full text |Cite
|
Sign up to set email alerts
|

A Multifrequency HYSCORE Study of Weakly Coupled Nuclei in Frozen Solutions of High-Spin Aquometmyoglobin

Abstract: In this work, we show the extreme power of multifrequency HYSCORE (hyperfine sublevel correlation spectroscopy) techniques to unravel the hyperfine interactions of the electron spin with the remote nuclei in the heme site of high-spin ferric heme proteins. Horse heart aquo-metmyoglobin was used as a model system to demonstrate the power of these techniques. Experimental evidence was collected and assigned to protons of the proximal histidine ligand, to the mesoprotons of the heme ligand, and to two different p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 40 publications
(101 reference statements)
1
12
0
Order By: Relevance
“…Glycerol was needed in this case as glassing agent to increase the electronic relaxation times and allow HYSCORE experiments. The overall HYSCORE features of the different Kp DyP variants are qualitatively in agreement with what was observed for other high-spin heme systems [ 37 , 38 , 39 , 40 , 41 , 42 ]. While the HYSCORE results are essentially the same for WT and D143A Kp DyP, subtle but significant difference were observed for R232A.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Glycerol was needed in this case as glassing agent to increase the electronic relaxation times and allow HYSCORE experiments. The overall HYSCORE features of the different Kp DyP variants are qualitatively in agreement with what was observed for other high-spin heme systems [ 37 , 38 , 39 , 40 , 41 , 42 ]. While the HYSCORE results are essentially the same for WT and D143A Kp DyP, subtle but significant difference were observed for R232A.…”
Section: Discussionsupporting
confidence: 87%
“…A previous in-depth study of aquometmyoglobin showed that the cross peaks related to the interaction of the electron spin with the N ε of the proximal histidine are usually weak or suppressed in the standard HYSCORE spectra, as is also observed here. At other magnetic-field settings, the matched 1 H HYSCORE spectrum reveals the characteristic cross-peaks due to the protons at the C ε and C δ positions of the proximal His ( Figure S8 ) [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…Unfortunately, we were unable to resolve any 14 N ENDOR resonances. In principle, the small couplings expected from the weakly interacting nitrogen nucleus in either coordination mode (i.e., A( 14 N py ) = [À1.14, À1.14, À0.53] MHz, Q( 14 N py ) = [0.44, 1.16, À1.60] MHz and A( 14 N NH 2 ) = [À0.82, À0.82, 0.26] MHz, Q( 14 N NH 2 ) = [0.82, 1.24, À2.06] MHz as predicted from the DFT calculations) should be resolvable by HYSCORE measurements, 25,41 although in this contribution we have focussed on the information available from the 1 H ENDOR data.…”
Section: Cw 1 H Endormentioning
confidence: 80%
“…In addition, overlapping HYSCORE signals require spectral subtraction [26] or relaxation filters [21,27]. More sensitive hyperfine measurements at Qband cannot substitute those at X-band as frequently both bands complement each other [24,25,28,29]. The SMART-HYSCORE sequence has been proposed to avoid blind spots and enable correlation of frequencies stemming from different nuclei [21,30], however, it usually necessitates long acquisition times on proteins (e.g.…”
Section: Hyscorementioning
confidence: 99%